New construction and reconstruction of the historic architectural environment in a view of zones of protection the monuments of architecture and town planning - Leshchenko, Nellya (Lira-K, 2016)
Conservation zoning is conducted and zones of protection of the monuments of architecture and town planning of the historic towns are established to protect the monuments and their surroundings, to preserve their compositional value and perspectives of view disclosure, to maintain the traditional character of planning and building of the historic environment. The article shows how the territory of the historical town is divided by the degree of the historical and cultural value of planning, building and landscape. The author analyzes the zones of protection of the monuments of architecture and town planning, reveals their task, shows, how the boundaries of these zones are established. The regime of reconstruction of the historical architectural environment in a view of conservation zoning of the historical city is determined in the article. The regeneration of the historical architectural environment applies to the territory of the monuments, to the complex protection zone and to the protection zones of separate monuments, located outside the historic center. In zones of building regulation is used the reconstruction regime with varying degrees of interference depending on the historical value of the environment around the monument and the remoteness of the site of designing from the monument.
Новое строительство и реконструкция исторической среды с учетом зон охраны памятников архитектуры и градостроительства
Keywords: the historical architectural environment; zones of protection of the monuments of architecture and town planning; reconstruction regime